"This Time We Shall Escape": Bob Dylan's Rolling Thunder Period. Issue 1 (2nd January 2016) - Hughes, John
Abstract : Bob Dylan's Rolling Thunder period—the two tours of 1975 and 1976 and Desire—manifests a significant shift in the subjective and cultural values of Dylan's creativity. The forward-looking ratios of critique and emancipation that had commonly marked the different phases of his 1960s' work have been replaced by themes and tropes of fate and escape. This betrays a certain belatedness that is all at once personal, cultural, and political in origin, and that reveals through Dylan's work at this time a politically significant and prevalent sense of subjectivity as a predicament rather than an opportunity.